The Supply Chain Collaboration Online Research Simulator - Dhariwal, Kewal; Carr, Peter (Proceedings of the International Conference on Networked Learning, 2004)
Supply chain collaboration is set to accelerate in future years. Evidence from a survey conducted with funding from the Canadian Purchasing Research Foundation is presented and it is argued that understanding of the exploitation of this environment is in its infancy. Recently Athabasca University commenced a research project on supply chain collaboration. Funded and supported by the Canadian Foundation for Innovation, the Alberta Provincial government, SAP and IBM, this project is focused on developing an online model of a fully data integrated supply chain. A simulation model is being used to help us learn how the business community will best use this supply chain environment of the future. Networked private communications between supply team members, data visibility, push versus pull systems, post-simulation performance analysis, group strategy formulation, strategy delivery and team discipline in networked environment are all aspects of research under consideration. A fully functional simulator of a data integrated supply chain environment supported by a complete range of online collaboration tools is currently being field tested and may be demonstrated at this symposium. It is available to researchers online throughout the world to develop their understanding of supply chain collaboration and networked resources management at www.athabascau.ca/scm or www.sccori.com